Analisis Kinerja Keuangan Lembaga Perkreditan Desa (LPD) Ambengan dengan Menggunakan Metode CAMEL - Yolanda Natalia Sinaga; Ni Wayan Ayu Santi (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to examine the financial performance of Lembaga Perkreditan Desa (LPD) Ambengan using the CAMEL method for the period 2021–2024. The research employs a descriptive quantitative method. The type of data used is quantitative data, with secondary data as the source. Data were collected through documentation and literature study. The subject of the research is the Lembaga Perkreditan Desa (LPD) Ambengan, while the object of the research is the financial statements. The data were analyzed using the CAMEL method, namely through the ratios of Capital, Assets, Management, Earnings, and Liability. The results show that the capital, assets, management, and liability ratios of LPD Ambengan during 2021–2024 fall into the “healthy” category, while the earnings ratio falls into the “unhealthy” category. Overall, the financial health level of LPD Ambengan for the period 2021–2024 is categorized as healthy.